Adsorption Of Doxycycline And Methylene Blue Onto Electric Arc Furnace (EAF) Steel Slag Derived Adsorbent - Abdullah, Amira Aziema (Universiti Sains Malaysia, 2017)
The aim of this work was to evaluate the adsorption capability of zeolite-kaolin and zeolite to remove Doxycycline, (DO) and Methylene blue, (MB) from aqueous solution. In this study, Electric-arc-furnace (EAF) steel slag which is a waste of steel making industry are used for formation of synthetic zeolite. Different kaolin ratios sample has been studied in order to obtain a better adsorbent by using 3 types of pharmaceuticals (Tetracycline (TR), Cephalexin (CP) and (DO)) and dye (MB). The adsorption performance of zeolite-kaolin for DO and zeolite for MB removal were tested by using a batch method. These studies had focussed on three parameters which are effects of initial concentration of pharmaceutical and dye solution (25 to 400 mgL⁄), temperature (30℃ to 50℃) and pH (3 to 13) on the adsorption of DO and MB. Freundlich and Langmuir isotherms were applied on the adsorption data showed that data are best fitted with Freundlich isotherm model for DO and MB solution. For adsorption kinetic, Pseudo-second-order kinetics proved that the adsorption process are much better than pseudo-first-order kinetics. The maximum adsorption capacity values of the zeolite-kaolin composite for DO were 188.95,289.00 and 356.70 mgg⁄ and the adsorption capacity values of the zeolite composite for MB were 101.75,120.40 and 139.35 mgg⁄ at 30,40 and 50℃, respectively. Based on the result obtained, it can be proved that the zeolite-kaolin and zeolite composite could provide basis for more low-cost composite to be used as adsorbents for pharmaceutical and dye removal.